(untitled) (Malaysian Journal of Civil Engineering, 2018)
Microbially induced calcite precipitation has been under investigation since early 1990s for its potential application in improving the strength and durability of construction materials such as limestone and cementitious materials. However, excellent results demonstrated by this technique in the studies so far conducted have shown greater potential of exploring its wider applications in geotechnical engineering. This study examines the microbial carbonate precipitations in tropical residual soil via urea hydrolysis. An isolate of urease active strain of Klebsiella pneumoniae UM123 was used to precipitates calcite into the soil with the aim of improving the strength and reducing the hydraulic conductivity of the soil. Cementation reagents concentrations of 0.25, 0.5, 0.75, 1.0 and 1.5M were used to evaluate the strength and hydraulic conductivity of the soil using treatment durations of 24, 48 and 60 hours. Meanwhile, bacteria concentrations of 1.5×104 cfu/ml and 2.9×106 cfu/ml were used to assess the effect of microbial concentrations in the study. The results obtained indicated a general increase in the strength of the treated soil as the bacteria concentrations increases. Likewise, the strength also increases with the increase in reagents concentrations up to 0.5M after which the strength declined. The hydraulic conductivity also decreased by 50% and 65% after 48 hours for 1.5×104cfu/ml and 2.9×106cfu/ml bacteria concentrations. The results so far obtained revealed that the optimum reagent concentration for this particular microorganism for efficient soil improvement is 0.5M.